Price Setting in Online Betting Markets: Evidence from the Eurovision Betting - HUASHENG XIANG (2021)
This thesis investigates the price-setting behaviour of bookmakers in the online betting market. Specifically, I study betting price dispersion, frequency, and magnitude of price changes, as well as bookmaker overround by employing betting prices for the Eurovision Song Contest 2017. Previous studies suggest that online betting markets are nearly frictionless and efficient, which implies that betting price dispersion should be negligible or at least diminishing over time, since time reveals the fundamental value of each bet. However, our empirical evidence shows that the extent of betting price dispersion is large and persistent. Even after accounting for the heterogeneity of bookmakers, the price dispersion survives. Crucially, betting prices are considerably sticky. For instance, the average duration of price spells is about 1.5 hours during the grand-final live, where the length of the grand-final is only 3.75 hours. By incorporating more than 600,000 related tweets, I find that the number of tweets is strongly positively associated with the frequency and magnitude of betting price changes. This shows that changes in betting prices reflect the information flow. Yet, little is known about the betting market friction; thus, more studies are needed. Finally, this thesis empirically examines the dynamic of bookmaker overround, which is helpful in understanding betting price-setting behaviour at the bookmaker level. I report a significantly positive correlation between the size of the overround and the degree of information uncertainty. Moreover, bookmakers tend to reduce the overround in the later progress of the contest, even after controlling the changes in the number of surviving participating teams. This implies that, when the outcome is more produced, bookmakers will attempt to increase their sales by reducing the overround. Consistent with the findings in sport betting markets, our results show that bookmakers adjust prices in a defensive manner by manipulating the size of the premium charged on each bet. For instance, the bookmakers increase their overrounds while the lower-ranked team is catching up with the higher-ranked team. Overall, this thesis provides a comprehensive analysis of bookmaker pricing at the good level and bookmaker level, respectively.